2013
DOI: 10.1007/s00125-013-3092-9
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to predefined dietary patterns and incident type 2 diabetes in European populations: EPIC-InterAct Study

Abstract: Aims/hypothesisFew studies have investigated the relationship between predefined dietary patterns and type 2 diabetes incidence; little is known about the generalisability of these associations. We aimed to assess the association between predefined dietary patterns and type 2 diabetes risk in European populations.MethodsFrom among a case-cohort of 12,403 incident diabetes cases and 16,154 subcohort members nested within the prospective European Prospective Investigation into Cancer and Nutrition study, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 47 publications
(68 reference statements)
3
44
0
Order By: Relevance
“…Yet, several other prospective studies reported null findings, e.g., the EPIC-InterAct study for the AHEI [32], the Health Professionals Follow-Up Study (HPFS) for the HEI [31], and the CARDIA study for the DQI [6]. Differences in range of index scores may partly explain discrepant findings across studies unless standardized scores are used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, several other prospective studies reported null findings, e.g., the EPIC-InterAct study for the AHEI [32], the Health Professionals Follow-Up Study (HPFS) for the HEI [31], and the CARDIA study for the DQI [6]. Differences in range of index scores may partly explain discrepant findings across studies unless standardized scores are used.…”
Section: Discussionmentioning
confidence: 99%
“…For the DASH index, two prospective studies in US populations described significant inverse associations with type 2 diabetes risk [5, 31], whereas a study in seven European countries detected no association [32]. Reasons for the discrepancy might be the use of study-specific categories in the DASH index and the consumption of foods specific to geographic environments, such as preferences for different types of meat in the US than European countries [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary risk factors have recently emerged: risk is increased by high consumption of red and processed meat 13 and sugar-sweetened beverages, 14 and reduced by intake of fruit and vegetables, 15 some types of dairy products, 16 and some overall dietary patterns. 17 Novel strategies to use quantifiable nutritional biomarkers are paving the way for more detailed understanding of the association between diet and diabetes. Although the heritability of type 2 diabetes is high (30–70%) and more than 60 genetic variants related with diabetes risk have now been identified, 18 the individual effects of genetic variants are modest, and even when combined into a genetic score, known genes contribute little to the prediction of diabetes.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…Such exploratory post hoc techniques aggregate intake variables into factors to reveal common underlying food consumption patterns within a population. 2 , 3 Because a posteriori–defined dietary patterns are derived specifically for the population under consideration, they are often not reproducible across populations. 1 Furthermore, a posteriori–defined patterns do not necessarily define the healthiest patterns because they are not derived from current nutritional knowledge or evidence-based diet–health relationships.…”
Section: Introductionmentioning
confidence: 99%